Tonsilitis Kronis Eksaserbasi Akut pada Anak Perempuan Usia 12 Tahun: LAPORAN KASUS - Ardian Reza Putra; Fitria Saftarina (Medula, 2026)
Chronic tonsillitis is a persistent inflammation of the tonsils resulting from recurrent infections and may undergo acute exacerbation, leading to more severe clinical manifestations. This condition is commonly encountered among school-aged children and may negatively affect quality of life, school performance, nutritional intake, and sleep quality. Contributing risk factors include recurrent upper respiratory tract infections, consumption of irritative foods and beverages, exposure to cigarette smoke, and poor oral hygiene. This case report aims to describe the clinical presentation, risk factors, management, and outcome of chronic tonsillitis with acute exacerbation in a pediatric patient. A 12-year-old girl presented with a three-day history of sore throat and odynophagia. The symptoms were accompanied by fever, foreign body sensation in the throat, cough, rhinorrhea, and decreased appetite. She had experienced recurrent episodes over the previous one and a half years, commonly triggered by fried foods, packaged snacks, and cold beverages. Physical examination revealed hyperemic tonsils with T2–T2 enlargement, irregular tonsillar surfaces, widened crypts, and positive detritus. Based on the history and physical findings, a diagnosis of chronic tonsillitis with acute exacerbation was established. The patient received paracetamol, amoxicillin, and dexamethasone, along with education regarding risk-factor modification and improvement of oral hygiene practices. One-month follow-up demonstrated significant clinical improvement without recurrence of symptoms. This case highlights the importance of identifying modifiable risk factors and providing comprehensive patient education as integral components of chronic tonsillitis management to reduce recurrence and improve clinical outcomes in pediatric patients.